Conceptualizations and instructional strategies on critical thinking in higher education: A systematic review of systematic reviews - Andreucci-Annunziata, Paola; Riedemann, Andrea; Cortés, Susana; Mellado, Augusto; del Río, María Teresa; Vega-Muñoz, Alejandro (Frontiers in Education, 2023)
Aim This systematic review identified systematic reviews of quantitative and qualitative empirical studies on the promotion and development of critical thinking in higher education students that allowed us to answer the following research questions: (1) What are the main definitions of critical thinking found in systematic reviews of critical thinking in higher education, and what are their similarities and differences? and (2) What are the most commonly used teaching strategies in higher education for teaching or promoting critical thinking, and how effective have they proven to be? Methods Systematic reviews were selected according to the guidelines for systematic reviews and meta-analyzes (PRISMA, 2020) and the eligibility criteria proposed by the PICOS strategy (population, interventions, comparators, outcomes and study design), based on 23 records of scientifically identified registers in the Journal Citation Report databases of the Web of Science. Results The bibliometric and systematic search of reviews of empirical studies on the topic allowed the selection of five systematic reviews. The results highlighted that conceptually critical thinking is related to both dispositions and skills, and that although there is no consensus on its definition, it is established that it is a higher-order cognitive process that can be trained. However, the results show that more studies have been conducted considering critical thinking as a skill than as a disposition, that the immersion approach has been widely used, and that some instructional strategies have shown greater effectiveness than others when the disciplines are evaluated independently. Discussion Despite the relative consensus on the importance of critical thinking for professional development in higher education, this review highlights some difficulties in conceptualizing critical thinking, in the relationship between dispositions and skills, and in its assessment in academic disciplines.